Only Walking for transportation in large Latin American cities : Walking-only trips and total walking events and their sociodemographic correlates - Delclòs-Alió, Xavier; Rodríguez, Daniel A; Medina, Catalina; Miranda, J. Jaime; Ávila-Palencia, Ione; Targa, Felipe; Moran, Mika R; Sarmiento, Olga Lucía; Quistberg, D. Alex (Taylor & Francis, 2022)
Walking for transportation is a common and accessible means of achieving recommended physical activity levels, while providing important social and environmental co-benefits. Even though walking in rapidly growing urban areas has become especially challenging given the increasing dependence on motorized transportation, walking remains a major mode of transportation in Latin American cities. In this paper we aimed to quantify self-reported walking for transportation in Mexico City, Bogota, Santiago de Chile, Sao Paulo, and Buenos Aires, by identifying both walking trips that are conducted entirely on foot and walking events involved in trips mainly conducted on other means of transportation (e.g., private vehicle, public transit) among individuals 5-years old. We show how walking-only trips account for approximately 30 percent trips in the analyzed cities, and we evidence how the pedestrian dimension of mobility is largely underestimated if walking that is incidental to other transportation modes is not accounted for: when considering all walking events, we observed an increase between 73 percent and 217 percent in daily walking time. As a result, authors estimated that between 19 percent and 25 percent of residents in these cities meet the WHO physical activity guidelines solely from walking for transportation. The results of the study also suggest that the promotion of public transportation in large Latin American cities can especially help certain population groups achieve the daily recommended levels of physical activity, while among low-income groups accessibility and safety seem to be the key challenge to be addressed.